Complexities Social Studies of Knowledge Practices - Andrew, Barry; Annemarie, Mol; Charis, Thompson; Chunglin, Kwa; John, Law; Laurent, Thévenot; Law, John; Marilyn, Strathern; Michel, Callon; Mol, Annemarie; Nick, Lee; Smith, Barbara Herrnstein; et al. (Duke University Press, 2002)
Although much recent social science and humanities work has been a revolt against simplification, this volume explores the contrast between simplicity and complexity to reveal that this dichotomy, itself, is too simplistic. John Law and Annemarie Mol have gathered a distinguished panel of contributors to offer-particularly within the field of science studies-approaches to a theory of complexity, and at the same time a theoretical introduction to the topic. Indeed, they examine not only ways of relating to complexity but complexity in practice.Individual essays study complexity from a variety of perspectives, addressing market behavior, medical interventions, aeronautical design, the governing of supranational states, ecology, roadbuilding, meteorology, the science of complexity itself, and the psychology of childhood trauma. Other topics include complex wholes (holism) in the sciences, moral complexity in seemingly amoral endeavors, and issues relating to the protection of African elephants. With a focus on such concepts as multiplicity, partial connections, and ebbs and flows, the collection includes narratives from Kenya, Great Britain, Papua New Guinea, the Netherlands, France, and the meetings of the European Commission, written by anthropologists, economists, philosophers, psychologists, sociologists, and scholars of science, technology, and society.Contributors. Andrew Barry, Steven D. Brown, Michel Callon, Chunglin Kwa, John Law, Nick Lee, Annemarie Mol, Marilyn Strathern, Laurent Thévenot, Charis Thompson
Description based on online resource; title from PDF title page (publisher's Web site, viewed 12. Dez 2020)
Keywords: PHILOSOPHY / Epistemology; Complexity (Philosophy); Knowledge, Sociology of